In-season changes in ventricular morphology and systolic function in adolescent female athletes. Issue 4 (21st April 2018) - Watson, Andrew M.; Coutinho, Carol; Haraldsdottir, Kristin; Brickson, Stacey; Dunn, Warren; Eldridge, Marlowe
Abstract: Purpose: To evaluate the influence of physical maturity on the changes in ventricular morphology and function with sport training in female youth athletes. Methods: Thirty-two female athletes (age 13–18 years) underwent height and weight measurement and 2-D echocardiographic evaluation immediately prior to, and following, a 20-week soccer season. Pre- and post-season left ventricular end-diastolic diameter (LVEDD), end-diastolic volume (LVEDV), ejection fraction (LVEF), stroke volume (LVSV), mass (LVM), and posterior wall thickness (LVPWT), right ventricular end-diastolic diameter (RVEDD), end-diastolic area (RVEDA), and fractional area change (RVFAC), and interventricular septal thickness (IVST) were compared. In-season change in each variable was compared across pre-season hours of vigorous physical activity (0–1, 2–3, >3 hours). Results: Significant increases were identified in LVEDV (51.3 ± 10.4 v 56.4 ± 9.6 ml/m 2, p  = 0.001) and RVEDA (10.5 ± 1.9 v 11.3 ± 2.5 cm 2 /m 2, p  = 0.040), but not LVEDD, LVM, LVPWT, LVSV, RVEDD, RVEDA, RVFAC, or IVST ( p  > 0.05 for all). In-season changes in echocardiographic variables did not differ across hours of pre-season vigorous physical activity ( p  > 0.05 for all). Conclusion: Among female adolescent soccer players, in-season training elicits changes in resting ventricular volume, but not wall thickness or systolic function. These adaptations do not appear to be influenced by pre-season physical activity level.